The geography of forest diversity and community changes under future climate conditions in the eastern United States. Issue 1 (2nd April 2016) - Bauer, Adam; Farrell, Rachel; Goldblum, David
ABSTRACT: Using modeled geographic range and importance projections of 133 tree species in the eastern United States we compare regional scale patterns of forest species diversity, similarity, evenness and community composition under present conditions with two future climate change scenarios. Overall, there is an increase in tree species richness on a pixel-by-pixel basis under future conditions, with a general shift to higher diversity in the northern portion of the United States. Percent similarity in species composition between current forest composition and future species composition under the low scenario averages 53.1%, and is lower for the high climate change scenario (45%), with the lowest similarity occurring in northern forests and the northern United States forest-prairie ecotone. In the future, species evenness increases over a large portion of the study area compared with current conditions. Forest community composition is stable in the southeastern United States, lower Great Lakes region and western extent of the eastern forests. Novel species assemblages develop in northern Wisconsin and Michigan, the northeastern United States, the southern forest-prairie ecotone and the southern coastal plain. Our study highlights geographic regions likely to experience substantial shifts in species composition and forest structure that should be monitored for early signs of forest change.